Penerapan media pembelajaran big book untuk meningkatkan keterampilan membaca permulaan peserta didik kelas 1 sekolah dasar - Tri Utami; Sukarno Sukarno; Muhammad Ismail Sriyanto (Universitas Sebelas Maret, 2019)
The aim of this research was to improve early reading skills by applying Big Book as a learning media on the first grade student of SDN Laweyan No. 54 Surakarta in academic year of 2018/2019. The research design was classroom action research which was conducted in two cycles. The subject of the research were teacher and first grade students of SDN Laweyan No. 54 Surakarta in academic year of 2018/2019 which amounted 25 students. Data collection techniques used interview, observation, documentation, and test. The data was analyzed with interactive analysis model by Miles and Huberman. The data validity was investigated through content validity, source triangulation, also technical triangulation. The result of the research showed that the implementation of Big Book as a learning media could improve the early reading skills on the first grade student of SDN Laweyan No. 54 Surakarta in academic year of 2018/2019. The improvement can be known from the amount of student who passed the minimum completeness criteria (≥75). The percentage of classical completeness in the pre-cycle was 44%, increased to 64% in the first cycle, then in the second cycle it raised to 84%.Keyword: Early Reading Skills, Big Book as A Learning Media